2020
DOI: 10.3390/plants9070846
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Metal Contamination and Potential Uptake by Phragmites australis Adans. (Poaceae) Along a Subtropical River System

Abstract: : Metal pollution is pervasive across terrestrial and aquatic ecosystems owing to anthropogenic activities. Sediments can accrue high concentrations of metals and act as secondary sources, and thus may be valuable indicators of metal contamination across spatiotemporal scales. In aquatic systems, the extent of metal pollution may be further mediated by transference among sediments and living organisms, with plant metal contaminants potentially predictive of underlying sediment concentrations. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…According to Emenike et al [46], high metal concentrations were observed during the hot-dry season; similarly, our study showed a similar finding where some metal concentrations peaked during the hotdry season, suggesting that accumulation and concentration occur as the river recedes and evaporation significantly increases, whereas the pollutants/contaminants entering the system remain constant. In support of our findings, Netshiongolwe et al [19] also observed similar patterns in metal concentrations. In contrast with this study findings, Edokpayi et al [33] found that metal concentrations were high during the hot-wet season in the Mvudi River, which was attributed to changes in human activities across different seasons.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to Emenike et al [46], high metal concentrations were observed during the hot-dry season; similarly, our study showed a similar finding where some metal concentrations peaked during the hotdry season, suggesting that accumulation and concentration occur as the river recedes and evaporation significantly increases, whereas the pollutants/contaminants entering the system remain constant. In support of our findings, Netshiongolwe et al [19] also observed similar patterns in metal concentrations. In contrast with this study findings, Edokpayi et al [33] found that metal concentrations were high during the hot-wet season in the Mvudi River, which was attributed to changes in human activities across different seasons.…”
Section: Discussionsupporting
confidence: 93%
“…Phragmites australis was the least effective in translocating metals, although it showed accumulation of metals during the hot-dry and hot-wet seasons. Similarly, studies by Kassaye et al [40] and Netshiongolwe et al [19] observed that P. australis has an absorptive ability for heavy metals and tends to accumulate these metals within the roots. Furthermore, Kassaye et al [40] highlighted that S. corymbosus has the potential to absorb heavy metals from soils, and they mostly accumulate in its leaves.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several macrophyte species, including Eichhornia, Ludwigia, Polygonum, Pistia, Cyperus, Lemna, Elodea, Typha, and Azolla, have been used to study HM contamination dynamics in tropical aquatic environments [135,160,207,208]. Macrophytes are appropriate bioagents for the long-term monitoring of aquatic ecosystem health due to their sedentary nature, high diversity, abundance, ease of identification and handling, and tolerance to HM pollution [105,209,210]. Changes in the macrophyte community structure and composition can also be a valuable indicator of pollution trends and alterations of the stream water quality [184,211].…”
Section: Microphytes Periphyton and Macrophytesmentioning
confidence: 99%
“…Leachate poisoned surrounding soils and vegetables. Studies revealed that upstream heavy metal concentrations were higher than downstream due to the leaching process 11,24) . The heavy metal contents tested were lead, mercury, zinc, cadmium, chromium, arsenic, iron, nickel, cobalt, selenium, and copper.…”
Section: Leachate Formation and Effects On Humans And Soil In Dumpsit...mentioning
confidence: 99%